1993
DOI: 10.1111/j.1349-7006.1993.tb02778.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Observation of Rat Prostate Lesion Development Induced by 3,2′‐Dimethyl‐4‐aminobiphenyl and Testosterone

Abstract: 3,2′‐Dimethyl‐4‐aminobiphenyl (DMAB), when combined with high doses of testosterone propionate (TP) induces invasive adenocarcinomas with metastatic potential in the rat prostate. The processes underlying this tumor development, including the involvement of atypical hyperplasias, were sequentially investigated in F344 rats. DMAB was given subcutaneously at a dose of 50 mg/kg body weight 10 times at 2‐week intervals. TP was administered chronically (in Silastic tubes) from the beginning of the experiment or aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…The incidences of the neoplastic lesions in the control diet group were comparable to those previously reported. 6,7,22) In the ventral prostate, no adenocarcinomas were found. In the dorso-lateral and anterior prostate, the isoflavone mixture supplement decreased the incidence of adenocarcinomas, but the differences were not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidences of the neoplastic lesions in the control diet group were comparable to those previously reported. 6,7,22) In the ventral prostate, no adenocarcinomas were found. In the dorso-lateral and anterior prostate, the isoflavone mixture supplement decreased the incidence of adenocarcinomas, but the differences were not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…Rats were given AIN-76A basal diet (Dyets Inc., Bethlehem, PA) or basal diet containing 100 and 400 ppm soybean isoflavone mixture and water ad libitum. Experimental procedure The experiment was performed according to the protocol established by Shirai et al, 22) as shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…Various findings have eluciules and development of metastases. 22,23 In addition, dated that androgens are deeply involved in the proShirai et al showed that, although carcinogenesis in motion step, including the fact that prostate carcinothe ventral lobe is androgen-dependent, there is a mas shrink in size after castration 2 and the fact that strong possibility that carcinogenesis in the other porthe plasma testosterone level or 5-alpha reductase actions of the accessory sex organs has lost its androgentivity is significantly elevated in races showing a high dependence in the early phase in spite of the fact that incidence of prostate carcinoma. [18][19][20][21] promotion by TP is essential.…”
Section: Discussionmentioning
confidence: 97%
“…Shirai et al (1991) established an experimental animal model of prostate cancer by exposure to 3,2′-dimethyl-4-aminobiphenyl (DMAB) and testosterone propionate (TP). In this model, carcinomas were observed from week 40 and thereafter increased in a time-dependent fashion until week 60 (Shirai et al 1993(Shirai et al , 1994. However, Shirai (1995) reported that this model had androgenindependent properties, despite the promotion effects of testosterone.…”
Section: Introductionmentioning
confidence: 89%